Antioxidant activity of propolis extract and its incorporation into a cosmetic formulation - Benavidez, Lita E. (2018)
The objective of the study was to evaluate the antioxidant activity of propolis extract and elaboration of a cremagel cosmetic formulation. The antioxidant activity of the propolis extract was determined by neutralization of the 1,1-diphenyl-2-picryl-hydrazyl radicals (DPPH˙ ++) and the 2,2'-azinobis (3-ethylbenzthiazolin) -6-sulphonic acid (ABTS) ˙ +). The extract showed antioxidant activity by the methods DPPH = 89.15 μg / mL and ABTS˙ + = 1069.18 μg / mL obtaining a lower result than the value of a reference study trolox EC50 = 5.04 μg / mL and EC50 = 17, 04 μg / mL respectively. With the extract a natural cosmetic formulation was designed in the form of cremagel, to which was added propolis extract as the main ingredient. For this formulation, an anionic acrylic copolymer dispersed in carrier oil, the propolis extract and no preservative was used. The pH result of the gel cream was 6.81. The formulation passed the initial centrifugation test for two hours at 3200 rpm and remained intact for one month of preliminary stability in an oven at 40 ° C; no separation of phases or breakage of the emulsion was evident. It is concluded that the propolis extract has antioxidant activity and is apt to develop natural cosmetic formulations.